Nano rare-earth oxides induced size-dependent vacuolization: an independent pathway from autophagy - Ying Zhang (Dove Medical Press, 2010)
Ying Zhang, Chenguang Yu, Guanyi Huang, Changli Wang, Longping WenHefei National Laboratory for Physical Sciences at Microscale, and School of Life Sciences, University of Science and Technology of China, Hefei, ChinaAbstract: Four rare earth oxides have been shown to induce autophagy. Interestingly, we often noticed plentiful vacuolization, which was not always involved in this autophagic process. In this study, we investigated three other rare-earth elements, including Yttrium (Y), Ytterbium (Yb), and Lanthanum (La). Autophagic effect could be induced by all of them but only Y2O3 and Yb2O3 could cause massive vacuolization. Y2O3 and Yb2O3 treated by sonication or centrifugation to reduce particle size were used to test vacuolization level in HeLa cell lines. The results showed that rare earth oxides-induced vacuolization is size-dependent and differs from autophagic pathway. To further clarify the characteristics of this autophagic process, we used MEF Atg-5 (autophagy associated gene 5) knockout cell line, and the result showed that the autophagic process induced by rare earth oxides is Atg-5-dependent and the observed vacuolization was independent from autophagy. Similar results could also be observed in our tests on 3-methyladenine(3-MA), a well-known autophagy inhibitor. In conclusion, for the first time, we clarified the relationship between massive vacuolization and autophagic process induced by rare earth oxides and pointed out the size effect of rare earth oxides on the formation of vacuoles, which give clues to further investigation on the mechanisms underlying their biological effects.Keywords: size-dependent, rare-earth oxides, vacuolization, autophagy